2017
DOI: 10.1007/s00203-017-1456-0
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in Beauveria bassiana infection to Galleria mellonella

Abstract: The ascomycete fungus Beauveria bassiana is a natural pathogen of hundreds of insect species and is commercially produced as an environmentally friendly mycoinsecticide. Many genes involved in fungal insecticide infection have been identified but few have been further explored. In this study, we constructed three transcriptomes of B. bassiana at 24, 48 and 72 h post infection of insect pests (BbI) or control (BbC). There were 3148, 3613 and 4922 genes differentially expressed at 24, 48 and 72 h post BbI/BbC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…Results showed that the survival of both insects was highest at 48 h BbI, but decreased dramatically at 60 h BbI, reflecting intense fungus–insect interactions at ∼ 48 BbI. This suggests that a critical period of host–pathogen interaction occurs before 48 BbI …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Results showed that the survival of both insects was highest at 48 h BbI, but decreased dramatically at 60 h BbI, reflecting intense fungus–insect interactions at ∼ 48 BbI. This suggests that a critical period of host–pathogen interaction occurs before 48 BbI …”
Section: Resultsmentioning
confidence: 93%
“…P. xylostella is a global insect pest that attacks crucifers, particularly cabbage, broccoli and cauliflower. Although previous studies have shown that thousands of B. bassiana genes were differentially expressed in the infection courses of both G. mellonella and P. xylostella , differences between infection strategies were unknown . Therefore, in this study, we attempted to investigate the transcriptomic differences that occur in B. bassiana at different infection stages when it infects G. mellonella and P. xylostella .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. bassiana kills the infected host by mechanical destruction of the host tissues with the growing mycelium and by the action of secreted secondary metabolites (Vilcinskas et al ., ; Fang et al ., ; Gibson et al ., ). Recently, genes involved in B. bassiana infection of G. mellonella have been identified (Fan et al ., ; Chen et al ., ). The set of genes whose expression level changes upon the infectious process depends on the host (Zhou et al ., )…”
Section: Introductionmentioning
confidence: 97%